ANALISIS INDIKATOR MASUKAN PROGRAM PEMBERANTASAN DEMAM BERDARAH DENGUE DI DINAS KESEHATAN PROVINSI SUMATERA UTARA - Izzah Dienillah Saragih; Reinpal Fahlefi; Devi Juliana Pohan; Sri Rezeki Hartati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2019)
Dengue Hemorrhagic fever (DHF) is a major public health problem in Indonesia where the number of reported cases per February 2019 reached 16.692 cases with 169 deaths. North Sumatera is an endemic area of dengue fever with a number of cases in 2017 of 5.454 and an IR number of 49 per 100.000 higher than the national target figure. Challenges on input indicators make the DHF eradication program run less optimally. Method: This research  was an qualitative study, which research design was a case study. The location taken in this study at the North Sumatera Provincial Health Office, the study was conducted from October to December 2018. The informants studied were 2 people. The research subjects were taken based on purposive sampling. Data collection techniques are carried out by in-depth interviews and observations, with research instruments in the form of interview guidelines and observation guidelines. Results: Analysis of input indicators in the DHF  eradication program at the North Sumatra Provincial Health Office found findings of Human Resources consisting of 2 doctors, 1 sanitarian staff and 1 expert epidemiologist (S2), still lacking funds in the DHF program. and the infrastructure of the DHF program consists of 2 liters of insecticide, 100 Rapid tests, 300 bottles of larvacide, and extension media in the form of banners. Conclusions and suggestions: Input indicators on the eradication program of dengue hemorrhagic fever at the North Sumatra Provincial Health Office have been fulfilled, namely on human resources and infrastructure, while the challenges of the DHF program in the North Sumatra Provincial Health Office are funding and counseling media. Suggestions for the North Sumatra Health Office, the allocation of funds needs to be evaluated as well as requests for allocation of funds to the center according to the ideal funding allocation.